Migration of Toxic Metals from Ceramic Food Packaging Materials into Acid Food Simulants. (26th May 2014) - Dong, Zhanhua; Lu, Lixin; Liu, Zhigang; Tang, Yali; Wang, Jun
Abstract : Long-term extraction experiments were carried out on glazed tile specimens with 4 and 10% (v/v) acetic acid, 1% (w/v) citric acid, and 1% (v/v) lactic acid solution in three temperature conditions (20, 40, and 60°C) to investigate the effect of temperature and pH value on extraction of lead, cobalt, nickel, and zinc from ceramic food packaging materials and to study the extraction kinetics of toxic metals. Results showed that except at 60°C the amount of extraction of lead, cobalt, nickel, and zinc had linear dependence on time at longer times and removal of these toxic metals under other conditions increased linearly with the square root of the time, indicating a diffusion-controlled process. The amount of these toxic metals leached out from ceramic food packaging materials into the leachate, and the leaching rate increased with temperature and decreased with pH value of the food simulants. In addition, among these four toxic metals lead was the least leachable element, and nickel was the most leachable one. Disagreement between the ratios of the oxide of lead, cobalt, nickel, and zinc in the glaze and their release in the leachate suggested that extraction of these toxic metals was an incongruent dissolution process.